Association between lower air pressure and the onset of ischemic colitis: a case–control study. Issue 9 (September 2017) - Kimura, Takefumi; Shinji, Akihiro; Tanaka, Naoki; Koinuma, Masayoshi; Yamaura, Maki; Nagaya, Tadanobu; Joshita, Satoru; Komatsu, Michiharu; Umemura, Takeji; Horiuchi, Akira; Wada, Shuichi; Tanaka, Eiji
Abstract : Objective: Ischemic colitis (IC) often affects the elderly. Proarteriosclerotic factors, such as hypertension and smoking, and cardiovascular disease are considered major contributors to IC. Although a possible link between certain cerebrocardiovascular disorders and meteorological phenomena has been reported, the relationship between IC onset and weather changes remains uninvestigated. This study examined whether specific meteorological factors were associated with the occurrence of IC. Patients and methods: We retrospectively enrolled 303 patients who had been diagnosed with IC between January 2003 and June 2010 at Suwa Red Cross Hospital in Nagano Prefecture, Japan. The meteorological data of the days on which IC patients visited the hospital (IC+ days) were compared with those of the days on which IC patients did not (IC− days). Results: Univariate analysis indicated that IC+ days had significantly lower air pressure ( P <0.001), depressed air pressure from the previous day ( P <0.001), and fewer daylight hours ( P <0.001), as well as higher air temperature ( P =0.017), air humidity ( P =0.004), wind velocity ( P <0.001), and rainfall ( P =0.012) compared with IC− days. Multivariate logistic regression analysis of the meteorological data showed that air pressure (odds ratio: 0.935, P <0.001) and change in air pressure from the previous day (odds ratio: 0.934, P <0.001) were related to onset of IC. Conclusion: Lower air pressure and decrease in air pressure from the previous day are possible novel factors associated with the development of IC.